Understanding Teachers' Experiences with Large-Scale Diagnostic Assessments in Indonesian Islamic Primary Schools: A Phenomenological Study - Retnawati, Heri; Hidayati, Kana; Dewantara, Andi Harpeni (Journal of Teaching and Learning, 2026)
This study explores teachers' experiences with and follow-up on large-scale diagnostic assessments in Indonesia, specifically the Indonesian Madrasah Competency Assessment (AKMI). A phenomenological approach within a qualitative methodology was adopted. Six 5th-grade teachers from an Indonesian Islamic Primary School participated. Data were collected through focus group discussions (FGDs). Data analysis was conducted in four steps: decontextualization, recontextualization, categorization, and compilation, to identify the content's underlying meanings. Key findings include: (1) teachers acquired administrative knowledge (e.g., test content management) and technical skills (e.g., student data management); (2) teachers' assessment understanding varied significantly but remained predominantly traditional rather than diagnostic; and (3) follow-up efforts primarily involved socialization and school programs, rather than instructional improvement. The study implies an urgent need to align assessment systems with classroom practice.